Living and Dead Aboveground Biomass in Mediterranean Forests: Evidence of Old-Growth Traits in a Quercus pubescens Willd. s.l. Stand - Emilio Badalamenti (Forests, 2017)
For a long time, human impact has deeply simplified most of the forest ecosystems of the Mediterranean Basin. Here, forests have seldom had the chance to naturally develop a complex and multilayered structure, to host large and old trees and rich biological communities, approaching old-growth conditions. Also for this reason, limited information is currently available about Mediterranean old-growth forests, particularly with regard to deadwood. The main aim of this work is to help fill this critical knowledge gap. In Sicily (Italy), we identified a Quercus pubescens forest that seemed to show some typical old-growth features. Total living volume (360 m3 ha−1) and basal area (34 m2 ha−1) were, respectively, about 6 and 3 times higher than the averages recorded in the regional forest inventory for this forest type. Deadwood was particularly abundant, exceeding the threshold of 30 m3 ha−1, mainly represented by lying dead elements. Dead to live wood ratio reached 9%, a value close to the threshold of 10% considered for Mediterranean old-growth forests. As the investigated forest showed some typical old-growth traits, it deserves to be fully protected and could be a permanent monitoring area for studying deadwood and stand dynamics in mature Mediterranean stands.